Focus on the Internet of Burkina: Measurement and Characterization - T. Ouédraogo, Frédéric; Zerbo, Boureima (International Journal of Computer (IJC), 2016)
Understanding the Internet topology and its modeling is important for many applications. In this paper we focus on a local area of the Internet topology at the scale of a country, to study its properties and characterize this local topology. We discuss our results compared to usual assumptions on the properties of Internet topology. Our study shows non trivial results. As a fractal, we find on a small scale of the Internet topology, some properties of the entire Internet like the power-law degree distribution and a weak density.